Team teaching in large spaces: three case studies framed by relational agency. Issue 3 (3rd July 2022) - Prain, Vaughan; Emery, Sherridan; Thomas, Damon; Lovejoy, Valerie; Farrelly, Cathleen; Baxter, Lindy; Blake, Damian; Deed, Craig; Edwards, Marie-Christina; Fingland, Doug; Mooney, Amanda; Muir, Tracey; et al.
ABSTRACT: Despite many claimed benefits, teacher collaboration remains patchy, under-theorised, and resisted. At the same time, new large teaching spaces offer teachers opportunities to teach in teams within and across school subjects to enhance teacher and student learning. In this paper we aim to contribute to theorising the nature and means of this form of collaboration, drawing on both relevant literature and analyses of three case studies of team teaching. We found that team teaching (a) is enabled and constrained by multiple contextual factors, and (b) potentially changes and enhances the nature and scope of teacher professional learning.